A luta pela terra e na terra: desafios e perspectivas do cooperativismo - Fazenda São Domingos, Tupaciguara (MG) - Cardoso, Lucimeire de Fátima (2012)
The heterogeneity of subjects, the worldview and the complex relationships that are (re)constructed in the settlements has shown us a scenario permeated by conflicts, resistance, advances and retreats, intrinsic to human relationships with these with their territories, which are responsible for the development and progress of the fight on the ground in our country. The struggle for land in Brazil has advanced slowly, especially if we consider only the measures that are taken in order to cool the tensions generated by the movements. The rural settlements are created as mitigation measures and they have faced all sorts of difficulties, both in implementation and development. From this perspective, rather than the struggle for land, social movements have realized the importance of fighting for the permanence and survival on the land. Thus, understanding the cooperatives, its difficulties and potentialities have been an important mechanism for thinking about a project for sustainable and collective development. Then, we took the settlement in the São Domingos Farm in Tupaciguara (MG), with the primary goal to understand the cooperative model adopted by the Labor Land and Freedom Movement (MTL), from the analysis of the experience of families in the implementation area of this project. The COERCO Santo Domingo, cooperative located in that settlement has represented possibilities, but also clashes and confrontations between the individuals involved. Understanding the relationship between the settlers and the movement was important, as well as the details of the resistance and the questioning of the model introduced by MTL, which is a process that can hinder or even derail the project as proposed.